การพัฒนาโปรแกรมสุขศึกษาโดยใช้แนวคิดการเรียนรู้เพื่อสร้างสรรค์ด้วยปัญญาและแบบแผนความเชื่อด้านสุขภาพเพื่อสร้างเสริมความฉลาดทางสุขภาพด้านผลิตภัณฑ์สุขภาพของนักเรียนอาชีวศึกษา - ปุณรัตน์ พิพิธกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
The purposes of this study were to 1) develop a Health Education Program based on constructionism concept and health belief model for enhancing health literacy on health products of vocational education students 2) study the effectiveness of this Health Education Program. The participants were 70 vocational education students divided into 2 groups of 35 students, an experimental and a control group.  The process of experiment took 8 weeks with 2 periods a week, and 60 minutes per period. The research instruments were health education program and health literacy questionnaire of the content validity assessed by 5 experts. The statistics used in data analysis for pretest and posttest were mean, standard deviation (S.D.) and t-test.The results of the research were as follows: 1) The developed health education program was a program of health education learning process in the area of health products of vocational education students which consisted of concepts, objectives, learning management process and evaluation. For learning management process, 2 components were organized (1) learning activity management in accordance with 4 steps (information sharing, connecting experiences, constructing works and reflecting of learning and presenting their works) by arranging 8 learning activities including principles of using health products, risk factors from health products, health literacy from health products, health products and our body, why using health products?, get away from unhealthy products, don’t let’s unhealth product into our life, and self-care of health products ; and (2) learning experience management in the areas of exhibition and guidance of health products. 2) Index of item-objective congruence (IOC) showed 0.90. After participating the program, health literacy mean scores of the experimental group were found significantly higher than before participating the program at the very good level and health literacy mean scores of the experimental group were also found significantly higher than the control group at .05 level.